Economic Diversification in the Gulf Region, Volume I The Private Sector as an Engine of Growth (The Political Economy of the Middle East,, 2018)
This volume focuses on the role of the private sector in diversifying the economics of Gulf countries in the post-petrodollar era, when fluctuating and declining oil prices are negatively impacting national expenditures. It explores current policies of countries in the Gulf Cooperation Council and their efforts to shift their economies away from heavy dependence on hydrocarbons. The structural changes will create favorable conditions for the private sector to flourish, shift production dependence from public to private sector, and allow for more efficient resource allocation. Such changes will also allow local banks to provide financial support to small and medium enterprises, boost entrepreneurship for job creation, and strengthen organizational structure and efficiency. This is the first volume in Economic Diversification in the Gulf Region.